2020
DOI: 10.1002/ccd.28839
|View full text |Cite
|
Sign up to set email alerts
|

Association of left ventricular end‐diastolic pressure with mortality in patients undergoing percutaneous coronary intervention for acute coronary syndromes

Abstract: Objectives: This study sought to investigate the relation between left ventricular end-diastolic pressure (LVEDP) and outcomes in patients undergoing percutaneous coronary intervention (PCI) for acute coronary syndromes (ACS). Background: Risk stratification in ACS patients is important. Data on the role of LVEDP in the prognostication of ACS patients are scarce. Methods: A total of 1,410 patients undergoing PCI for ACS and with available data on LVEDP were divided according to LVEDP tertiles (lowest tertile: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…There is a significant association between LV systolic wall stress and LV oxygen demand, with peak systolic wall stress identified as one of the primary factors associated with myocardial oxygen demand and, consequently, LV performance [2]. More recently, an association has been identified between elevated LV end diastolic pressure and mortality in acute coronary syndromes [3]. While early reperfusion aims to reoxygenate myocardium at risk, some have posited that it may be more effective to first pursue a strategy of reducing myocardial oxygen demand by means of LV unloading [4,5].…”
mentioning
confidence: 99%
“…There is a significant association between LV systolic wall stress and LV oxygen demand, with peak systolic wall stress identified as one of the primary factors associated with myocardial oxygen demand and, consequently, LV performance [2]. More recently, an association has been identified between elevated LV end diastolic pressure and mortality in acute coronary syndromes [3]. While early reperfusion aims to reoxygenate myocardium at risk, some have posited that it may be more effective to first pursue a strategy of reducing myocardial oxygen demand by means of LV unloading [4,5].…”
mentioning
confidence: 99%
“…The Impella (Impella, Abiomed Inc., Danvers, MA) is a microaxial pump delivering blood from the left ventricle forward into the ascending aorta. It is inserted through the femoral route (13)(14) or it can be placed surgically through the axillary artery. Once the access site has been achieved [34], it is advanced from the aorta into the LV.…”
Section: Percutaneous Lv-to-aorta Circulatory Support: Impellamentioning
confidence: 99%
“…However, reduced LV function increases the likelihood of hemodynamic instability during complex PCI procedures [ 12 ]. Finally, LV end-diastolic pressure represents an easy-to-obtain invasive measure of cardiac compensation and has been demonstrated to significantly stratify mortality in invasively managed acute coronary syndromes [ 13 ]. In this regard, an accurate evaluation of diastolic function in the preprocedural setting might be of pivotal importance for risk stratification, alongside LV systolic function ( Table 1 ).…”
Section: High-risk Pci: Definition and Hemodynamicsmentioning
confidence: 99%
“…Studies have found significant prognostic value in predicting short‐term all‐cause mortality in patients with STEMI using admission‐shock index (SI = HR/SBP), modified shock index (MSI = HR/mean arterial pressure [MAP]), Age‐SI (SI multiplied by age) and Age‐MSI (MSI multiplied by age) 9‐12 . Invasively measured hemodynamic parameters such as left ventricular end‐diastolic pressure (LVEDP) have also been shown to predict mortality in STEMI 13‐17 . Moreover, it is theoretically attractive that coronary perfusion pressure (CPP) which can only be calculated with invasive hemodynamic measurements, would provide important prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Invasively measured hemodynamic parameters such as left ventricular end-diastolic pressure (LVEDP) have also been shown to predict mortality in STEMI. [13][14][15][16][17] Moreover, it is theoretically attractive that coronary perfusion pressure (CPP) which can only be calculated with invasive hemodynamic measurements, would provide important prognostic information. Thus, the current study tested the hypothesis that shock indices could be improved by incorporating invasive hemodynamic measurements using a novel shock index incorporating values of HR, age and CPP that are readily available during PPCI.…”
mentioning
confidence: 99%